Monocyte and CD4+ T-cell antiviral and innate responses associated with HIV-1 inflammation and cognitive impairment. (15th July 2020) - Sharma, Vishakha; Bryant, Christopher; Montero, Maria; Creegan, Matthew; Slike, Bonnie; Krebs, Shelly J.; Ratto-Kim, Silvia; Valcour, Victor; Sithinamsuwan, Pasiri; Chalermchai, Thep; Eller, Michael A.; Bolton, Diane L.
Abstract : Objective: Mechanisms underlying immune activation and HIV-associated neurocognitive disorders (HAND) in untreated chronic infection remain unclear. The objective of this study was to identify phenotypic and transcriptional changes in blood monocytes and CD4 + T cells in HIV-1-infected and uninfected individuals and elucidate processes associated with neurocognitive impairment. Design: A group of chronically HIV-1-infected Thai individuals ( n  = 19) were selected for comparison with healthy donor controls ( n  = 10). Infected participants were further classified as cognitively normal ( n  = 10) or with HAND ( n  = 9). Peripheral monocytes and CD4 + T cells were phenotyped by flow cytometry and simultaneously isolated for multiplex qPCR-targeted gene expression profiling directly ex vivo . The frequency of HIV-1 RNA-positive cells was estimated by limiting dilution cell sorting. Results: Expression of genes and proteins involved in cellular activation and proinflammatory immune responses was increased in monocytes and CD4 + T cells from HIV-1-infected relative to uninfected individuals. Gene expression profiles of both CD4 + T cells and monocytes correlated with soluble markers of inflammation in the periphery ( P  < 0.05). By contrast, only modest differences in gene programs were observed between cognitively normal and HAND cases. These included increased monocyte surface CD169 protein expression relative to cognitively normal ( P  = 0.10), decreased surface CD163 expression relative to uninfected ( P  = 0.02) and cognitively normal ( P  = 0.06), and downregulation of EMR2 ( P  = 0.04) and STAT1 ( P  = 0.02) relative to cognitively normal. Conclusion: Our data support a model of highly activated monocytes and CD4 + T cells associated with inflammation in chronic HIV-1 infection, but impaired monocyte anti-inflammatory responses in HAND compared with cognitively normal. Abstract : Supplemental Digital Content is available in the text